The Effect of Good Corporate Governance Structure, Company Size, and Profitability on Audit Delay in Manufacturing Companies: Empirical Study from the F&B Sub-Sector on IDX - Ai Hopipah Parawangsa; Syakieb Arsalan (Golden Ratio of Auditing Research, 2026)
This study employs a descriptive, quantitative approach, drawing on secondary data from audited financial statements and annual reports. The research sample was selected using a purposive sampling method, comprising 37 companies and 111 observations. GCG structure was measured using the independent board of commissioners, audit committee, and institutional ownership; company size was measured using the natural logarithm of total assets; and profitability was measured using Return on Assets (ROA). Audit delay was measured as the number of days between the end of the fiscal year and the date of the independent auditor's report. The results indicate that the GCG structure had no significant effect on audit delay. Company size had a positive effect on audit delay, while profitability had a negative and significant effect. These findings indicate that company characteristics, particularly size and profitability, play a greater role in determining audit timeliness than GCG structure. This study is expected to provide practical implications for management and auditors in improving the efficiency and timeliness of audit completion.